A simulation exercise for incorporating long-term path dependencies in urgent decision-making. (September 2021) - Järvensivu, Paavo; Räisänen, Helmi; Hukkinen, Janne I.
Highlights: The exercise incorporates long-term path dependencies in urgent decision-making. The exercise integrates utilitarian and emancipatory dimensions. The exercise enables experiential and social learning of decision-making in crises. The exercise helps decision-makers to navigate wicked socio-ecological disruptions. Abstract: Urban policymakers of the 2020s must act within various types of wicked socio-ecological disruptions. Under deep uncertainty and time pressure, they must make decisions which will define the scope of possible actions in the future. Our aim was to develop a research instrument that would enable researchers and practitioners to learn about such policymaking. We designed and ran a half-day simulation exercise, the Policy Operations Room (POR). The participants were the top politicians and a group of senior experts from the City of Helsinki, Finland. The design of the exercise was based on a review of simulation and gaming research literature. The exercise managed to integrate – albeit imperfectly – the utilitarian and emancipatory dimensions in futures studies: it gave the participants the utilitarian possibility to practice decision-making and the emancipatory possibility to critically reflect on decision-making in wicked, science-based scenarios. It also gave the researchers a chance to witness urgent decision-making in action. Issues deserving further attention include the inclusion of social-political complexity in the scenarios and practitioner involvement in the design process of the exercise. All in all, the POR constitutes a unique way of integrating science-based assessment of future path dependencies into science–policy research and interaction.